New in The Tropical Agriculturalist series [2] - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Donkeys, by D. Fielding and P. Krause, CTA/Macmillan co-publication 1998, 120 pp., ISBN 0-333-62750-4, 10 credit points.